Optical Modeling Analysis of Red, Green, and Yellow Phosphors with a Blue LED - Wen-Shing Sun; Chuen-Lin Tien (Advances in Condensed Matter Physics)
The luminous properties of red, green, and yellow phosphors with a blue LED are evaluated and a corresponding optical model is constructed using the optical simulation software LightTools®. According to the phosphor particle model, the desired chromaticity coordinate of the multicomponent light which is excited by a blue LED can be achieved by modifying the weight concentration of the phosphors. A comparison of the four types of LED package modules tested shows that the yellow phosphor encapsulated with a semispherical module takes up a lesser percentage of the total weight percentage of a constructed white light with a correlated color temperature of around 4000 K. The simulation and experimental results provide a cross-reference for better packaging and encapsulating designs for lumen improvement.